THE PRICE CONTROVERSY OF MINYAKITA: MEDIA, POLICY, AND PUBLIC OPINION PERSPECTIVES - Retno Dewi Zulaikah; Samsudin; Lukita Permanasari (el Hakim Press, 2024)
The price controversy surrounding Minyakita has remained a persistent public concern. As a subsidized cooking oil product designed to assist low-income communities, Minyakita is often unavailable at the government-set Maximum Retail Price (MRP). This situation raises significant questions about the effectiveness of distribution policies and food governance in Indonesia. Various factors, including long distribution chains and limited inter-agency coordination, serve as major obstacles to maintaining price stability and product availability in the market. This study aims to analyze the roles of mass media, government policies, and public opinion in shaping the dynamics of the controversy. Using a qualitative approach with descriptive and case study methods, the research draws on primary data from in-depth interviews, field observations, and secondary data from news articles and policy documents. The findings indicate that media coverage tends to be fragmented and focused on sensational aspects, reinforcing negative public perceptions of the government. The implementation of the Maximum Retail Price (MRP) policy is hindered by the lengthy distribution chain and inadequate logistics infrastructure. Additionally, the allocation of export levy funds for CPO prioritizes biodiesel subsidies over Minyakita production subsidies, leading to supply instability. Public opinion, influenced by policy inconsistencies, has eroded trust in the government, while market stability is particularly disrupted in rural areas. The study concludes that reforms in distribution policies, optimization of producer incentives, increased transparency, and improvement in the media's role in delivering data-driven information are essential to resolving this controversy. Recommendations include optimizing distribution infrastructure, reallocating export levy funds, and developing consistent public communication strategies. This research is expected to contribute to strengthening the national food system and enhancing public trust in the government.